Mitogenome evolution in the Lacerta viridis complex (Lacertidae, Squamata) reveals phylogeny of diverging clades. Issue 7 (3rd October 2021) - Jauss, Robin-Tobias; Solf, Nadiné; Kolora, Sree Rohit Raj; Schaffer, Stefan; Wolf, Ronny; Henle, Klaus; Fritz, Uwe; Schlegel, Martin
Abstract : In order to elucidate mitochondrial evolution and resolve the phylogeny of the widely distributed European green lizards ( Lacerta viridis complex), we determined 16 mitochondrial genomes from a representative sampling of the four previously identified major clades corresponding to L. bilineata (western distribution range), L. viridis (most of the eastern distribution range), the unnamed Adriatic (or West Balkan) and the Turkish + south-eastern European clades. The mitogenomes were on average 17, 162 bp long with a canonical vertebrate gene inventory of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes and a long non-coding Control Region. We detected several almost completely clade-specific insert and tandem-repeat signatures. Phylogenetic analyses using all 13 protein-coding genes as well as rRNA- and tRNA-coding sequences from a total of 20 mitogenomes inferred a resolved branching pattern of the four divergent clades. The Turkish clade is strongly supported as sister to all other members of the complex. Within the monophylum comprising the remaining clades, L viridis is sister to a clade containing L. bilineata and the Adriatic clade. Unexpectedly, one specimen of western Italy (Calambrone, Pisa) – which is within the distribution range of L. bilineata – clustered together with the Adriatic clade with high bootstrap support, calling for further research on the biogeography of the L. viridis complex. Integrating our results with those of previous studies suggest that the lineages have reached the level of distinct taxa, but to determine whether they have become fully independent lineages on the species level requires further research that tackles nuclear genomic variation of all four clades and the viability of hybrids and gene flow within putative hybrid zones.